Local Communities Perception on Rural Tourism (Global Journal of Human-Social Science, 2012)
This paper presents a review of attributes for rural tourism to be a sustainable tourism product It also covers an overall review and conceptualization of rural tourism within the community development perspective Rural tourism involves activities that make the rural community to directly engage in tourism either by them having full control or having their culture serves as the attraction Evidence shows that very few studies have attempted to understand the impact of tourism from the rural peoples point of view Focusing on the community s participation is very important as they are the industry s key players involved in tourism An extensive study of the literature on the local peoples perception and participation in tourism business is essential to draw a crystallized conceptual framework The understanding of the rural communities opinion on perceived impacts is important before implementing any tourism related development by the outsiders The developed framework will be useful to understand the hosttourism system and relationship that will emphasize co-management approach to promote a sustainable tourism practice
Keywords: local community; rural tourism; perception; sustainable tourism